2016
DOI: 10.18632/oncotarget.14121
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-guided targeting of GPR55 for anti-cancer therapy

Abstract: Expression of the lysophosphatidylinositol receptor GPR55 correlates with invasive potential of metastatic cells and bone metastasis formation of different types of tumors. These findings suggest a role for GPR55 signaling in cancer progression, including in lymphoproliferative diseases. Here, we screened a M13-phage-displayed random library using the bait of HEK293 cells that heterologously expressed full-length HA-GPR55. We selected a set of phagotopes that carried 7-mer insert peptides flanked by a pair of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…Prolonged LPI stimulation induces GPR55 down-regulation from the plasma membrane [38]. Time-course of LPI-induced internalisation of overexpressed ssGPR55 in HeLa cells indicated that this process started in the rst few minutes of LPI stimulation, and reached a plateau after 10 min (Fig.…”
Section: Lpi-dependent Gpr55-mediated Signal Transductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Prolonged LPI stimulation induces GPR55 down-regulation from the plasma membrane [38]. Time-course of LPI-induced internalisation of overexpressed ssGPR55 in HeLa cells indicated that this process started in the rst few minutes of LPI stimulation, and reached a plateau after 10 min (Fig.…”
Section: Lpi-dependent Gpr55-mediated Signal Transductionmentioning
confidence: 89%
“…Based on the sequence of peptide-P1 (CKKNSPTLC), both a scrambled peptide (Scr; KCLTSNCPK) with the same amino-acid composition as peptide-P1 but a different primary sequence, and an irrelevant peptide (Irr_P; CGGNGPGLC) that included mutations to all of the polar amino acids of peptide-P1, were designed. All of the peptides were cyclised using an intramolecular disulphide bond between the two cysteine residues [38]. The uorescent peptides were obtained by conjugation at the N-terminus with uorescein-isothiocyanate (FITC) with an aminohexanoic acid linker.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations